Causal impact of gut microbiota on five liver diseases: insights from mendelian randomization and single-cell RNA sequencing - Li, Na; Chen, Xuanyi; Xiong, Shuai; Cheng, Yuxin; Deng, Jiali; Zhang, Junli; Yu, Fei; Hao, Liyuan; Li, Shenghao; Hu, Xiaoyu (Frontiers in Genetics, 2024)
BackgroundLiver disease is among the top ten causes of death globally. With studies suggesting a link between gut microbiota (GM) and liver disease.MethodWe selected summary statistics data from the largest available whole-genome association study (n = 13,266) of GM by the MiBioGen consortium as the exposure, and obtained liver disease-related data from IEU Open GWAS and The NHGRI-EBI GWAS Catalog. A two-sample Mendelian Randomization (MR) analysis employing various methods, to establish the causal relationship between GM and five liver diseases. Meanwhile, single-cell RNA sequencing data were used to examine Prevotella-related genes expression under healthy and disease liver.ResultsThe IVW analysis indicate a causal relationship between GM and liver diseases, with Prevotella exhibiting a protective effect in all five liver diseases: Alcoholic liver disease (OR:0.81,95% confidence interval:0.66-1.00,PIVW = 0.0494); Cirrhosis (OR: 0.85,95% confidence interval: 0.73-0.99,PIVW = 0.0397); Hepatic failure, not elsewhere classified (OR:0.60,95% confidence interval:0.37-0.95,PIVW = 0.0305); Benign neoplasm:Liver (OR:0.39,95% confidence interval:0.2-0.75,PIVW = 0.0046); Malignant neoplasm of liver, primary (OR:0.41, 95% confidence interval:0.18-0.93,PIVW = 0.0334). The single-cell results suggest differential expression of Prevotella-related genes between liver disease patients and healthy individuals.ConclusionOur MR results show a causal relationship between the GM and liver disease. Prevotella displays a notable protective effect. This finding may enhance the precision of GM-based therapies and offer new insights for clinical research.